Kerjasama Indonesia-Nigeria dalam Menangani Jaringan Perdagangan Narkoba Nigeria di Indonesia. Periode 2015-2017 - Perdana, Yonathan Addo Putra; Utomo, Tri Cahyo (Journal of International Relations, 2020)
As a country of more than 260 million people, Indonesia has a strong market appeal, including for drug trafficking networks. Therefore, Indonesia is no longer seen merely as a transit country, but rather as a destination country (main destination). There were many cases of trafficking and drug use in Indonesia, until President Joko Widodo at the beginning of his government in 2014 declared Indonesia a drug emergency. One of the largest syndicate networks supplying drugs to Indonesia comes from Nigeria. Therefore, Indonesia needs cooperation with Nigeria in order to overcome the rampant drug trafficking in the country. A bilateral cooperation needed in dealing with drug trafficking was finally realized in the signing of a Memorandum of Understanding (MoU) signed in Abuja in February 2013.This study aims to analyze the form and results of Nigeria's cooperation with Indonesia related to the Nigerian network of drug trafficking in Indonesia in the period 2015 to 2017. The type of research is descriptive qualitative, while data collection is conducted by interview, observation and documentation study. The author uses the Liberalism theory to discuss about this issue. This research shows that the cooperation between Indonesia and Nigeria resulting number of case involving Nigerian people in Indonesia is decreasing